GAME AS FACILITATOR IN DEVELOPMENT OF PHONOLOGICAL PERCEPTION FOR PRESCHOOL CHILDREN - Tūbele, Sarmīte; Vilka, Ilze (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Language is the highest form of communication, it’s given only to people and it is very important for children’s psychological development. In 5 – 6 years most of the children all native language’s sounds pronounce correctly, phonological perception is formed, however, not all children have reached an appropriate level of development, therefore compulsory preparatory school program of language acquisition in children creates an aversion to learning. Disorders of fonological perception are very complicated and require a lot of serious and patient work in the intervention. In 5 – 6 years of age, children are active, open, spontaneous, curious and very persistent. At this age closest activities for children are plays and games and in these activities they acquires their own life experience.